2004
DOI: 10.1001/archotol.130.2.195
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Quality of Life and Respiratory Disturbance After Extended Uvulopalatal Flap Surgery in Patients With Obstructive Sleep Apnea

Abstract: To evaluate the subjective and objective outcomes of extended uvulopalatal flap (EUPF) surgery in patients with obstructive sleep apnea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 18 publications
0
21
0
3
Order By: Relevance
“…Both UPPP and the flap showed comparable results with regard to effectiveness for OSA, amount of tissue removed and complications. Six papers investigated the effect of an isolated uvulopalatal flap without any other surgeries at the same time [241,[244][245][246][247][248]. The AHI decreased significantly from 45 to 14 within 6-12 months after surgery.…”
Section: Overview Of the Evidencementioning
confidence: 99%
“…Both UPPP and the flap showed comparable results with regard to effectiveness for OSA, amount of tissue removed and complications. Six papers investigated the effect of an isolated uvulopalatal flap without any other surgeries at the same time [241,[244][245][246][247][248]. The AHI decreased significantly from 45 to 14 within 6-12 months after surgery.…”
Section: Overview Of the Evidencementioning
confidence: 99%
“…Briefly, animals were housed in Plexiglas boxes with free access to food and water and exposed 7 h/day for 14 days to either E-IH (20 brief exposures/h to 5% O 2-5% CO2) or air-air cycling (sham, constant stream of room air). We have demonstrated that this protocol lowers PO2 to ϳ35 mmHg with no change in PCO2 (37), simulating moderate to severe sleep apnea where O2 saturation falls as low as 70% (22,23). Body weight, systolic blood pressure (SBP), and heart rate were recorded on days 0 and 14 before the start of the daily E-IH or air-air exposure using a standard tail-cuff apparatus (IITC).…”
Section: Animalsmentioning
confidence: 99%
“…It reduces the risk of nasopharyngeal incompetence and is associated with less postoperative pain. It is however contraindicated in patients with excessively long or bulky soft palate 51,52 . UPPP lowers the positive airway pressure requirements, thus improving CPAP compliance in selected patients 53 .…”
Section: Uvulopalatopharynoplasty (Uppp)mentioning
confidence: 99%